The shield ring. - Sutcliff, Rosemary (New York H. Z. Walck, 1972)
A young girl witnesses the waning power of the Norse in their continuing conflict with the Normans in eleventh century England.
Keywords: Great Britain -- History -- Norman period, 1066-1154 -- Juvenile fiction; Great Britain -- History -- Norman period, 1066-1154 -- Fiction